2022
DOI: 10.1155/2022/6805501
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Nanosemiconductor Materials on Thermal Stability of Solar Cells

Abstract: In order to overcome the problem of long-term stability of perovskite solar cells, the author proposes a method to study the effects of nanosemiconductor materials on the thermal stability of solar cells. In this method, n = 3 and n = 1 (C6H5(CH2)2NH3)2(CH3NH3)n-1Pbn I3n+1 two-dimensional nanoperovskite films were investigated on glass substrates and indium tin oxide (ITO) substrates, respectively, on the thermal stability. Experimental results show that the glass-based nanoperovskite PMPI3 film was partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%